Growth and Plant Architecture of Several Introduced Coffea canephora Clones Under Different Shade Levels - Yuliasmara, Fitria; Sumirat, Ucu; Wicaksono, Karuniawan Puji; Widaryanto, Eko (Indonesian Coffee and Cocoa Research Institute, 2022)
Introducing superior plants is one of the efforts to increase coffee produc- tivity in Indonesia. Three clones from France de Torino (FRT), FRT 07, FRT 09, and FRT 65, have been introduced to Indonesia. However, their cultivation is not widely distributed yet. Analysis of the responses of FRT clones against differences in climate and cultivation is needed to determine the right cultivation system to produce maximum growth and productivity. This study examines the vegetative growth of FRT clones introduced at some levels of shade. The study employed a split-plot design with 36 experimental units. The primary factor was the levels of shade consisting: without shade, 25% of shade, 50% of shade, and 100% of shade. The three introduced FRT clones (FRT 07, FRT 09, and FRT 65) were used as the subplot. Observations were done on several growth variables. The results showed that shade treatment affected all growth parameters and plant architecture. Clones significiantly affected plant height, orthotropic internode length, number of leaves, and average leaf area. Increased levels of shade caused an increase in internode length, branch angle, and crown diameter but decrease in number of internodes and leaves. A low level of shade (25%) produced an optimal value on parameters related to the productivity of FRT coffee plants, such as the number of plagiotropic internodes and the number of leaves. Parameters related to vegetative growth, such as plant height, stem diameter, and internode length, showed optimal values in a moderate level of shade (50%). Treatment without shade and a heavy shade resulted in impaired growth of FRT coffee. There was no interaction between levels of shade and clone treatment on most of the variables related to plant morphology, which indicated that the three introduced FRT clones gave relatively similar response to shade; thus, the three clones can be managed with the same shade management.